Application of management tools aiming to reduce losses in the production process in a capixaba glass factory - Carvalho, Flavio Lucio Santos de; Mattos, Tiago de Nardi (Brazilian Journal of Production Engineering, 2022)
The current scenario requires companies to optimize processes, whether in the use of tools, use of raw materials, or even the hiring of employees, providing lean production. Thus, attention to processes is of great importance, to reduce not only lead times but also losses during product manufacturing. Based on the ideal of reducing waste, this study aims to identify the sector where the greatest losses occur and act to minimize or eliminate these loss indicators in the evaluated production process. In order to reach the results through the research, several data from the factory’s production process were collected, such as monthly losses, the monthly quantity produced and the employees’ income during the execution of activities. By applying the Pareto Diagram, SWOT Matrix, Ishikawa Diagram, 5W’s 2H’s, and PDCA cycle tools, it was possible to identify the critical point of the process and quantify the losses guiding decision-making. Thus, an action plan was developed to work in the glass cutting sector, the initial sector with the largest input and output volume of orders in the organization during the production process.